Handbook of cyanobacterial monitoring and cyanotoxin analysis - Meriluoto, Jussi; Spoof, Lisa; Codd, G. A. (Geoffrey A.); European Cooperation in the Field of Scientific and Technical Research (Organization) (Chichester, West Sussex : John Wiley & Sons, Inc., 2017)
A valuable handbook containing reviews, preactical methods and standard operating procedures. A valuable and practical working handbook containing introductory and specialist content that tackles a major and growing field of environmental, microbiological and ecotoxicological monitoring and analysis Includes introductory reviews, practical analytical chapters and a comprehensive listing of almost thirty Standard Operating Procedures (SOPs) For use in the laboratory, in academic and government institutions and industrial settings
Section I: Introduction -- Section II: Cyanbacteria -- Section III: Sampling, monitoring and risk management -- Section IV: Toxins and bioactive/noxious compounds from cyanobacteria -- Section V: Screening and trace analysis of cyanotoxins -- Section VI: Methodological conosiderations -- Section VII: Standard operating procedures (SOPs) -- Section VIII: Appendices.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cyanobacteria; Cyanobacterial blooms -- Monitoring; Cyanobacterial toxins; Cyanobacteria; Cyanobacterial blooms -- Monitoring; Cyanobacterial toxins; SCIENCE / Life Sciences / Biology; SCIENCE / Life Sciences / Microbiology; Cyanobacteria; Electronic books; Electronic books